A custom-made distal humerus plate fabricated by selective laser melting. Issue 6 (26th April 2021) - Thomrungpiyathan, Thansita; Luenam, Suriya; Lohwongwatana, Boonrat; Sirichativapee, Winai; Nabudda, Kriengkrai; Puncreobutr, Chedtha
Abstract: This study aims to evaluate the mechanical performance of custom 3D-printed titanium plates in the treatment of distal humerus fractures. Rigidity of four plating configurations were investigated by finite element analysis. The results reveal that implementation of custom designs with minimal screw holes, lateral-medial linking screw and lateral brim could significantly improve stiffness and consequently leads to better biomechanical stability as compared to standard osteosynthesis design. Biomechanical testing was also performed to validate practical usability. The results confirm that newly designed custom plates fabricated by selective laser melting is a possible alternative for the treatment of distal humerus fracture.